Future of The City: Incorporation of Locust Bean Pod Ash and Groundnut Shell Ash in Self-Consolidating Concrete (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The research reports the inclusion of admixture to Self-Consolidating Concrete (SCC) to use locally sourced organic waste material as an alternative building material in reducing the burden of housing provision. Self-Consolidating Concrete (SCC) is a flowable type of concrete that doesn't require mechanical compaction. It uses high paste and fine aggregate content, small coarse aggregate size, and Supplementary Cementitious Materials (SCMs) to achieve this. SCC's adoption in construction projects has increased cement demand, which contributes to CO2 emissions and environmental issues. SCMs like Locust Bean Pod Ash (LBPA) and Groundnut Shell Ash (GSA) are being studied to improve SCC's properties. In this study, LBPA and GSA were used to replace 20% of cement in SCC mixes. Results indicate that LBPA and GSA are effective pozzolans, but at 20% replacement, they didn't enhance mechanical performance significantly. However, a mix with 75% GSA and 25% LBPA showed comparable performance at 28 days, with compressive strength of 33.64N/mm2 and split tensile strength of 3.91N/mm2. The fresh properties of the SCC mixes met EFNARC standards.